THE DISTRIBUTION OF CATECHOLAMINES BETWEEN PLASMA AND PLATELETS IN CYCLOSPORIN A-INDUCED HYPERTENSIVE RATS - Reis, F. (2000)
One of the most serious side effects of the immunosuppressive agent, cyclosporin A (CsA), is drug-related hypertension. As it is generally accepted, the sympathetic nervous system may play an important role in the development or maintenance of this abnormal pathophysiological situation. This study is aimed at assessing plasma and platelet catecholamines, and a possible connection to cyclosporin A-induced increased arterial blood pressure. It was thus based on an investigation in which Wistar rats were divided into three groups: one taking only orange juice (control) and the other two receiving 5 and 30 mg kg-1([`]trough' and [`]peak') of cyclosporin A (Sandimmun Neoral®), daily, for 7 weeks. Plasma and platelet noradrenaline, adrenaline and dopamine levels and arterial blood pressures were evaluated before the start of the study (week 0) and after 2, 4 and 7 weeks. Plasma and platelet catecholamines increased drastically in the [`]peak' CsA concentration-treated group, which contrasts with the slight decrease observed in the group treated with the [`]trough' concentration. However, both groups revealed an increase in blood pressures, when compared with the control group. These findings suggest that at least [`]peak' cyclosporin A concentration alters significantly the plasma and platelets catecholamines levels, which may contribute to the cyclosporin A-induced hypertension. Other contributions, regardless of catecholamine content disturbances, might occur, at least at [`]trough' CsA concentrations.